MEKANISME PEMBAYARAN PAJAK PENGHASILAN PASAL 22 PADA PT. RUKMINI MANDIRI - Fahrizal Adiyatma; Fahmi Roy Dalimunthe; Dwianto Mukhtar Latif (JRUP: JURNAL REFERENSI DAN ULASAN PERPAJAKAN, 2021)
The purpose of the study is to determine the mechanism for payment of Income Tax Article 22 PT. RUKMINI MANDIRI and to find out the implementation of the collection of Income Tax article 22 with the updated provisions.The data analysis method used is descriptive method, which is one method of data analysis that describes or describes a data that has been collected without being intended to make a generalization conclusion or that can be applied to the general public.The results of the study found that the mechanism for paying Income Tax Article 22 by PT Rukmini Mandiri was in accordance with the applicable law. PT. Rukmini Mandiri pays Article 22 Income Tax when ordering goods to Pertamina. The payment was made by PT. Rukmini Mandiri the day before the ordered goods arrived at the gas station. Payment is made to a bank appointed by the Minister of Finance in the amount of the value of the goods ordered added to the amount of Income Tax Article 22 payable. The rates charged for PT. Rukmini Mandiri as a private gas station is 0.3% (zero point three percent) for BioSolar, Premium, Dexlite, Pertamax, Bulk, and Pertalite. The reporting of Income Tax Article 22 is carried out by Pertamina no later than the 20th after the end of the tax period for all gas stations.